2003
DOI: 10.1186/1478-4491-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors for job motivation of rural health workers in North Viet Nam

Abstract: Background: In Viet Nam, most of the public health staff (84%) currently works in rural areas, where 80% of the people live. To provide good quality health care services, it is important to develop strategies influencing staff motivation for better performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
362
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(395 citation statements)
references
References 2 publications
29
362
0
4
Order By: Relevance
“…Other studies have also found that procedural justice was related to job attitudes, 25,33,34 including organisational commitment and trust in management and that inadequate management support and a sense of not being valued by their managers were strong features of the environment. Yet the role of managers in motivating and retaining staff is something that has largely been ignored in attempts to address the migration of health workers, even though managers who are unsupportive or inconsiderate can be a strong push factor.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies have also found that procedural justice was related to job attitudes, 25,33,34 including organisational commitment and trust in management and that inadequate management support and a sense of not being valued by their managers were strong features of the environment. Yet the role of managers in motivating and retaining staff is something that has largely been ignored in attempts to address the migration of health workers, even though managers who are unsupportive or inconsiderate can be a strong push factor.…”
Section: Discussionmentioning
confidence: 93%
“…All health facilities 34 in three districts in Malawi (one from each of the three geographical regions) were included in the sampling frame. The sample consisted of those willing to participate at the time the data collectors visited the facilities (Box 1).…”
Section: Sampling and Methodsmentioning
confidence: 99%
“…The main motivating factors for employees aside from having good job training, cordial relationship with colleagues and manager is appreciable income. The main discouraging factor aside from unimpressive working conditions is the payment of low income to employees [18]. Study done by Dieleman et al [18] was supported by Azman et al [19] where money acts as a moderating variable in the relationship between income distribution and pay satisfaction in the studied organization.…”
Section: Methodsmentioning
confidence: 83%
“…Key sources of motivation for physicians are professional autonomy [5,35] , achievement [6] , relationships with patients [4] , and interaction with colleagues [6,36] . Motivation of physicians is affected by both financial and non-financial incentives which should be considered together for long term results [36,37] . Policy makers need to recognize that motivation among physicians is complex and requires comprehensive approaches [3] .…”
Section: Discussionmentioning
confidence: 99%